2018
DOI: 10.1124/dmd.117.079194
|View full text |Cite
|
Sign up to set email alerts
|

Brain Distribution of a Novel MEK Inhibitor E6201: Implications in the Treatment of Melanoma Brain Metastases

Abstract: Clinically meaningful efficacy in the treatment of brain tumors, including melanoma brain metastases (MBM), requires selection of a potent inhibitor against a suitable target, and adequate drug distribution to target sites in the brain. Deregulated constitutive signaling of mitogen-activated protein kinase (MAPK) pathway has been frequently observed in melanoma, and mitogen-activated protein/extracellular signal-regulated kinase (MEK) has been identified to be an important target. E6201 is a potent synthetic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 46 publications
1
13
0
Order By: Relevance
“…PK study results showed that omeprazole has a moderate clearance (37.75 ± 5.05 mL/min/kg) in mice. The brain-to-plasma coefficient (Kp) was calculated to evaluate the efficiency of omeprazole passing through the brain [22,23]. The ratios between area under the curve (AUC last ) values from brain and plasma were used for the calculation (Equation 1) and as a result, the Kp value was 0.15 for i.v.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…PK study results showed that omeprazole has a moderate clearance (37.75 ± 5.05 mL/min/kg) in mice. The brain-to-plasma coefficient (Kp) was calculated to evaluate the efficiency of omeprazole passing through the brain [22,23]. The ratios between area under the curve (AUC last ) values from brain and plasma were used for the calculation (Equation 1) and as a result, the Kp value was 0.15 for i.v.…”
Section: Pharmacokinetic Studymentioning
confidence: 99%
“…If inferior pathway inhibition contributes to reduced response rates, there is the potential to overcome this through the use of higher doses of BRAFi + MEKi, a strategy which has been successfully used in the treatment of non‐small cell lung cancer brain metastases with EGFR mutations (Davies, ; How, Mann, Laczniak, & Baggstrom, ). Another strategy would be to develop and test BRAFi and/or MEKi with good blood–brain barrier or blood‐tumor penetration in the brain, such as the MEKi E6201, which is currently being studied in patients with BRAF‐mutant MBM (NCT03332589; Gampa et al, ). Alternatively, resistance could be caused by the activation of other signaling pathways in the tumor cells by the brain microenvironment, such as the aforementioned PI3K‐AKT and CDK4 pathways (Chen et al, ; Niessner et al, ).…”
Section: Targeted Therapymentioning
confidence: 99%
“…E6201, a synthetic analog of a natural product, is an ATP-competitive dual kinase inhibitor of MEK1 and FLT3 [10,11]. Preclinical studies showed that E6201 may be useful for treatment of cancers associated with elevation of MEK1 kinase activity, including melanoma and acute myeloid leukemia [12][13][14][15]. E6201 has been evaluated in a phase I clinical trial in advanced solid tumors and melanoma (trial registration ID: NCT00794781).…”
Section: Introductionmentioning
confidence: 99%